Use of PGPB in bio-fertilisation: preserving the soil microbiome and enhancing field production of alfalfa - Fernández-Pastrana, Vanesa Mercedes; Mora, Marina Robas; González-Reguero, Daniel; Probanza, Agustín; Iglesias, Diana Penalba; Gómez, Pedro Antonio Jiménez (Frontiers in Microbiology, 2026)
Sustainable fodder production requires fertilisers that increase yield without compromising soil ecology. We tested whether a humic-rich biofertiliser derived from valorised horticultural waste (ORGAON® PK) could be enhanced with two genomically screened plant-growth-promoting bacteria (PGPB) in a field trial with Medicago sativa. The crude residue substantially increased biomass, and the addition of Bacillus sp. C1 or Pseudomonas sp. C2 further redirected these gains towards improved fibre digestibility or greater protein and energy content. Soil microbial diversity was maintained, although community composition shifted towards taxa involved in organic-matter degradation and nitrification. Both inoculants persisted without displacing dominant native genera, and biofertilised soils showed reduced susceptibility to β-lactam antibiotics. Overall, pairing OPK with targeted PGPB enhanced forage yield and quality while supporting microbiome resilience, highlighting a promising One-Health-aligned alternative to mineral fertilisers. Multi-season trials are now needed to validate broader applicability.